Atlas of science: another view on science (AoS Nordic AB, 2017)
Atlas of Science provides the opportunity for scientists to write and publish a short and accessible summary (Layman summary) of their latest research. The summaries should be based on peer-reviewed articles.
Gesehen am 12.01.2017
Keywords: Website